n-Alkane hydroconversion on Zeogrid and colloidal ZSM-5 assembled from aluminosilicate nanoslabs of MFI framework type - Aerts, Alexander; Huybrechts, Ward; Kremer, Sebastien P B; Kirschhock, Christine E A; Theunissen, Elisabeth; Van Isacker, Annabel; Denayer, Joeri F M; Baron, Gino V; Thybaut, Joris W; Marin, Guy B; Jacobs, Pierre A; Martens, Johan A (Chemical communications (Cambridge, England), 2003)
n-Alkane hydroisomerisation and hydrocracking experiments reveal that ZSM-5 materials synthesized by self-assembly of nanoslabs show different molecular shape selectivity than ZSM-5 synthesized by hydrothermal methods.